Area Berisiko Limbah Domestik di Kota Kendari Tahun 2023: Pemodelan Spasial - Jumakil Jumakil (Program Studi S2 Kesehatan Masyarakat Universitas Halu Oleo, 2025)
Domestic waste in Kendari City was found dumped in yards around houses, dumped through open drainage, without any prior processing, the condition of the feces storage is also mostly still using the cubluk type, which on one side is not waterproof so that it has the potential to pollute the soil and groundwater around it. This study is a descriptive observational study with a Geographic Information System (GIS) approach. Data collection was carried out by household surveys using questionnaires and observation sheets. This study used a simple random sampling technique and there were 2,600 households selected as samples. The results of the study showed that the highest risk index occurred in 11 sub-districts, namely Mandonga, Labibia, Puuwatu, Benua Nirae, Poasia, Lalolara, Kendari Caddi, Kampung Salo, Mata, Purirani, and Jati Mekar. The lowest occurred in Anggolomelai Sub-district, the highest risk index value was 100, the lowest risk index value was 65.83. 33 sub-districts were included in the very high risk category, 21 high risk, 7 moderate risk, and 3 less risky. The conclusion is that sub-districts with a very high risk level are priority areas for intervention related to the improvement and handling of domestic waste in Kendari City